Calculation Model of Pipeline Resistance for Cemented Paste Backfill Considering Thixotropy - Chang, Yingjie; Zhang, Youzhi; Gan, Deqing; Wang, Xinyi; Du, Shuangcheng (Archives of Mining Sciences, 2022)
The rheological behaviour of cemented paste backfill (CPB) has an important influence on the stability of its transportation in pipelines. In the present study, the time-dependent rheological behaviour of CPB was investigated to elucidate the effects of time and solid content. Experimental results showed that when CPB is subjected to a constant shear rate, the shear stress gradually decreases with time before finally stabilis ing. When the solid content was 60%~62%, a liquid network structure was the main factor that influenced the thixotropy of CPB, and the solid content had less influence. When the solid content was 64%~66%, a floc network structure was the main factor that influenced the thixotropy of CPB, and the solid content had a more significant influence on the thixotropy than the shear rate. The initial structural stability of CPB increased with the solid content, and this relationship can be described by a power function. Based on the experimental results, a calculation model of pipeline resistance considering thixotropy was proposed. The model was validated by using industrial experimental data. The current study can serve as a design reference for CPB pipeline transportation.
Keywords: thixotropy; cemented paste backfill; pipeline transportation; calculation model; hydraulic gradient